1986
DOI: 10.1111/j.1559-3584.1986.tb00631.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Water Emulsified Fuel Investigations for Shipboard Applications

Abstract: A comprehensive summary of a survey on research into the theory and application of water-emulsified fuel is presented. Its potential impact on diesel, boiler, and gas turbine shipboard power plants is discussed in terms of fuel consumption, maintenance, emissions, and safety.Intermediate grade to heavy fuel oils emulsified with 6% to 10% water have the most potential for cost savings in shipboard propulsion systems. Maintenance is reduced in boilers and is significantly lower for all power plants. Water-emulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Many claims have been made for the use of fuel emulsions, such as reduction of fuel consumption, more complete combustion, and reduced exhaust emissions [2,3]. Studies have shown that using emulsion fuels in internal combustion engines is an effective method for the reduction of NO x , soot, and particulate emission [4][5][6], In addition, it was found that adding water to diesel fuel can lead to reduction of heat flux, metal temperatures, and the thermal loading of combustion chamber components [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many claims have been made for the use of fuel emulsions, such as reduction of fuel consumption, more complete combustion, and reduced exhaust emissions [2,3]. Studies have shown that using emulsion fuels in internal combustion engines is an effective method for the reduction of NO x , soot, and particulate emission [4][5][6], In addition, it was found that adding water to diesel fuel can lead to reduction of heat flux, metal temperatures, and the thermal loading of combustion chamber components [7].…”
Section: Introductionmentioning
confidence: 99%